Design and Analysis of Carbon Fibre Composite Monorack Arm for Motorcycle - Abd Hamid, Amar Ridzuan; Jagan, T (International Journal of Integrated Engineering, 2019)
Monorack arm in the motorcycle is invented for the support of external topbox. However, load-bearing of the typical monorack arm made of common engineering metals is restricted to only 3 kilogram in which exceeding this load may result in failure. Therefore, alternative materials such as carbon fibre composite receives the spotlight for this project. With that being said, the project objectives were to propose several conceptual designs of monorack arm which were used to analyze with finite element methods. Next, fabrication of carbon fibre composite sample was required to perform experimental analysis. Accordingly, 3 conceptual designs of monorack arm in regard to design considerations under static stress application were established. Besides, 2 types of samples were fabricated for experimental analysis namely plain weave woven fabric carbon fibre and twill weave woven fabric carbon fibre. Samples of carbon fibre composites were fabricated to possess a higher fibre volume fraction than the matrix to add fibre strength in the composite. Final conceptual designs of monorack made were computed for structural analysis using ANSYS Workbench. During the simulation of conceptual models, design 2 of epoxy carbon woven (230 GPa) wet was found to show better structural results in comparison to other designs using the same material. Lastly, tensile test was performed on the fabricated test specimens of plain weave carbon fibre and twill weave carbon fibre according to ASTM standards whereby favourable results were shown to plain weave woven fabric carbon fibre.